Duration of symptoms does not correlate with results of T‐cell gene rearrangement studies in patients evaluated for cutaneous T‐cell lymphoma. (29th May 2015) - Larson, Allison R.; Rodig, Scott; Granter, Scott R.
<x xml:space="preserve">Abstract</x> Objectives We aimed to determine if clonality on T‐cell gene rearrangement studies correlated with duration of cutaneous symptoms in patients with skin disease who are being evaluated for cutaneous T‐cell lymphoma (CTCL). Specifically, our goal was to determine if symptom duration could help better optimize sample selection for T‐cell gene rearrangement studies. Methods Biopsies were reviewed from patients within both general dermatology clinic and CTCL specialty clinic for clonality results in relation to disease duration. Results We did not find an association between duration and clonality in any group. Conclusions The yield of T‐cell gene rearrangement studies is similar between shorter and longer duration of disease implying that there is not an optimal duration range in which T‐cell gene rearrangement studies are more likely to give a positive result.